Endophytic non-pathogenic Fusarium oxysporum reorganizes the cell wall in flax seedlings - Wojtasik, Wioleta; Dymińska, Lucyna; Hanuza, Jerzy; Burgberger, Marta; Boba, Aleksandra; Szopa, Jan; Kulma, Anna; Mierziak, Justyna (Frontiers in Plant Science, 2024)
Flax (Linum usitatissimum) is a valuable crop producing valuable products like seeds and fiber. However, its cultivation faces challenges from environmental stress factors and significant yield losses due to fungal infections. The primary major threat is Fusarium oxysporum f.sp lini, causing fusarium wilt of flax. Interestingly, within the Fusarium family, there are non-pathogenic strains known as biocontrols, which protect plants from infections caused by pathogenic strains. When exposed to a non-pathogenic strain, flax exhibits defense responses similar to those seen during pathogenic infections. This sensitization process activates immune reactions, preparing the plant to better combat potential pathogenic strains. The plant cell wall is crucial for defending against pathogens. It serves as the primary barrier, blocking pathogen entry into plant cells. In conclusion, the research suggests that the rearrangement of the cell wall is likely one of the mechanisms behind flax sensitization by the non-pathogenic Fusarium oxysporum strain. Understanding these processes could help in developing strategies to enhance flax's resistance to fusarium wilt and improve its overall yield and quality.